Effects of dietary Bacillus velezensis fermented soybean hull supplementation on antioxidant capacity, suppressing pro-inflammatory, and modulating microbiota composition in broilers - Yung Hao Chen; Yi Chen Li; Shen Chang Chang; Min Jung Lin; Li Jen Lin; Tzu Tai Lee (Poultry Science)
This study aimed to ferment soybean hulls (SBH) with Bacillus velezensis and evaluate their effects on broiler diets, specifically focusing on intestinal antioxidant capacity, immune modulation, and microbiota composition. The animal trial involved 400 one-day-old Arbor Acres broilers, randomly assigned to a control group (basic diet, Control) and groups receiving 5 % and 10 % unfermented soybean hulls (5 % USBH, 10 % USBH) and 5 % and 10 % fermented soybean hulls (5 % FSBHB, 10 % FSBHB) as replacements for the basic diet. Each group contained 80 birds, divided into four pens with 20 birds per pen, and the trial lasted for 35 days. In the jejunum, the 5 % FSBHB group tended to suppress pro-inflammatory gene expression, while the 10 % FSBHB group tended to enhance antioxidant gene expression. In terms of jejunum protein levels, the 10 % FSBHB group exhibited significantly lower (P < 0.05) TNF-α protein levels compared to the control and other treatment groups. Furthermore, intestinal microbiota analysis showed that ileum and cecum microbial counts in the 10 % USBH and 10 % FSBHB groups were higher than those in the control group. Species richness indices also revealed that both the 10 % USBH and 10 % FSBHB groups were significantly higher (P < 0.05) than the control group. In conclusion, soybean hulls fermented with Bacillus velezensis improved intestinal antioxidant capacity, suppressed pro-inflammatory gene expression, and modulated microbiota composition in broilers, with the 10 % FSBHB group demonstrating the most pronounced effects.